PENGARUH EKSTRAKURIKULER PASKIBRA TERHADAP KARAKTER DISIPLIN SMP NEGERI 25 PEKANBARU - Hasanah, Nurul; Gimin, Gimin; Hambali, Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine whether the extracurricular activities of the paskibra affect the disciplinary character of students of Pekanbaru 25 Middle School. As for the population, there are 50 paskibra members.By using a saturated sample technique (Total Sampling) obtained 50 students selected to be the sample in this study. Data collection techniques are carried out through observation, documentation and questionnaires. The method used is descriptive quantitative method. The method is done by processing data whose data results are presented through a percentage of questionnaires that have been filled in by the respondents. In analyzing the data using simple linear regression analysis. The results of this study indicate that there is an extracurricular effect on paskibra on the disciplinary character of students of Pekanbaru 25 Middle School, this is evidenced by a series of simple linear regression tests between variables X and Y variables, obtained Fcount = 33.934 and Ftable 4.04 obtained from the study of the list of F distributions with N = 50, at a significant level of 5%, thus Fcount> Ftable or 33,934> 4.04, then H0 is rejected and Ha is accepted as significant, there is the influence of extracurricular paskibra on the disciplinary character of students of Pekanbaru 25 Middle School. Key Words: Influence, Paskibra Extracurricular, Discipline Character